A study of printed La₂O₃ on carbon-glass substrate for micro-flexographic printing process using angle resolve x-ray photoelectron spectroscopy (AEXPS) analysis - Hassan, S; Yusof, M S; Embong, Z; Maksud, M I (Malaysian Nuclear Society (MNS), 2020)
Micro-flexographic printing process involved in patterning technique from micron to nano scale range to be used for graphic, electronic and bio-medical device on variable substrates. Adhesive property of printing process could be described as an interchangeably with some ink or medium and substrate which was applied to one surface of two separate items that bonded together. Lanthanum oxide (La2O3) had been used as a rare earth metal candidate as printing ink medium. This metal deposit was printed on carbon-glass substrate. The choose of Lanthanum Oxide as a target is due to its wide application in producing electronic devices such as thin film battery and printed circuit board. The La2O3 deposited on the surface of carbon-glass substrate was then analyzed using Angle Resolve X-Ray Photoelectron Spectroscopy (ARXPS). The position for each synthetic component in the narrow scan of Lanthanum (La) 3d and O 1s are referred to the electron binding energy (eV). This research was focused on 3 narrow scan regions which are C 1s, O 1s and La 3d. Further discussion of the spectrum evaluation was discussed in detail. Here, it was proposed that from the adhesive properties of La was suitable as an alternative medium for micro-flexographic printing technique in printing multiple fine solid lines image at micro to nano scale feature. Hence, this paper will describe the capability of this particular metal as rare earth metal in a practice of micro-flexographic printing process.